Confidence Modulates the Conformity Behavior of the Investors and Neural Responses of Social Influence in Crowdfunding - Zheng, Jiehui; Hu, Linfeng; Li, Lu; Shen, Qiang; Wang, Lei (Frontiers in Human Neuroscience, 2021)
Decision about whether to invest can be affected by others’ choices or opinions, known as social influence. People make decisions with fluctuating confidence, which plays an important role in decision process. However, it remains a fair amount of confusion regarding the effect of confidence on social influence as well as the underlying neural mechanism. The current study applied a willingness-to-invest task with event-related potentials method to examine the behavioral and neural manifestations of social influence and its interaction with confidence in the context of crowdfunding investment. The behavioral results demonstrate that people’s conformity tendency increased when their willingness-to-invest deviated far from the group’s. Besides, when people felt less confident about their initial judgement, they were more likely to follow the herd. In conjunction with the behavioral findings, the neural results of social information processing indicate different susceptibilities to small and big conflicts between people’s own willingness and the group’s, with small conflict evoked less negative FRN and more positive LPP. Moreover, confidence only modulated the later neural processing by eliciting larger LPP in low confidence, implying more reliance on the social information. These results corroborate previous findings regarding conformity effect and its neural mechanism in investment decision and meanwhile extend the existing literatures through providing behavioral and neural evidence to the effect of confidence on social influence in crowdfunding marketplace.